Analisis Yuridis Perceraian Luar Pengadilan di Desa Nyormanis Kecamatan Blega Kabupaten Bangkalan Madura - Putri, Kurnia Dwi; Eka Saputri, Adinda Dian; Firdausi, Nurul; Chairun Nisa, Luthfia (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
Law in Indonesian has regulated the procedures for marriage, divorce, and reconciliation in Law No. 1 of 1974 concerning Marriage. And also stated in Law No. 22 of 1946 concerning the Recording of Divorce and Referrals. From the explanation contained in the positive law, it can be seen that the meaning of divorce is the breaking of the marriage ties of a married couple as a result of the failure to carry out the marriage due to several things such as death and court decisions. Divorce in law of Indonesian must be announced before the court. The pronouncement of divorce before the court is a mandate from article 115 of the Compilation of Islamic Law (KHI) which reads “Divorce can only be conducted in front of a Religious Court hearing after the Religious Court has tried and failed to reconcile the two parties.” But in fact, there are still many Indonesian people who do divorce not before the court. Divorce which is done outside the court is very negative, especially for the wife. Divorce is done only by word alone without going through a pledge in front of the court, then the state does not want to recognize the divorce, so that if the wife wants to remarry with another person, then it cannot be done because the wife does not have an official divorce certificate from the court. [Hukum Indonesia telah mengatur mengenai tata cara perkawinan, talak, maupun rujuk dalam Undang- Undang No. 1 Tahun 1974 Tentang Perkawinan. Serta tertera pula pada Undang-Undang No. 22 Tahun 1946 Tentang Pencatatan Talak dan Rujuk. Dari penjelasan yang termuat dalam hukum positif tersebut, dapat diketahui bahwa arti perceraian adalah putusnya ikatan pernikahan pasangan suami isteri sebagai akibat kegagalan menjalankan bahterah rumah tangga yang disebabkan oleh beberapa hal seperti kematian dan atas keputusan pengadilan. Perceraian dalam hukum Indonesia, harus diikrarkan di depan pengadilan. Pengucapan talak di hadapan pengadilan merupakan amanah dari pasal 115 Kompilasi Hukum Islam (KHI) yang berbunyi “ Perceraian hanya dapat dilakukan di depan sidang Pengadilan Agama setelah Pengadilan Agama tersebut berusaha dan tidakberhasil mendamaikan kedua belah pihak.” Akan tetapi dalam kenyataannya, masih banyak masyarakat Indonesia yang melakukan perceraian tidak di depan pengadilan. Perceraian yang diakukan di luar pengadilan sangat lah berdampak negatif, khususnya bagi isteri. Perceraian yang dilakukan hanya secara ucapan saja tanpa melalui ikrar di depan pengadilan, maka negara tidak mau mengakui peceraian tersebut, sehingga apabila si isteri ingin menikah lagi dengan orang lain, maka tidak bisa dilakukan karena isteri tidak memiliki akta perceraian secara resmi dari pengadilan.]